Estimation of efficiency of transportation organization of distribution systems - Онищенко, Светлана Петровна; Сираев, Александр Рафаилович; Самойловская, Валентина Петровна (Eastern-European Journal of Enterprise Technologies, 2012)
The article is devoted to the efficient organization of transportation services (on the example of maritime transport) of distribution systems of integrated industrial and commercial structures. The study of the efficiency of various transportation organizations is considered from the point of view of marketing, so the idea of ​​transportation is formed in conjunction with decisions on other issues of the organization of distribution systems. However, the majority of studies consider the transportation service in the logistics level, where the information is highly refined, and the parameters of supply are worked out in accordance with clearly defined set of conditions. Therefore, the basis of a solution to the problem is the analytical expression of profits from sales, taking into consideration specific (in terms of cost) transportation organizations. The suggested regularities are based on the dependence of economic indicators on the performance parameters of vehicles, the characteristics and requirements of different markets. Obtained summarized conditions of the preference of each transportation organization are designed to decide on outlets and delivery conditions